Lao PDR Economic Monitor, June 2018 : Safeguarding Stability - An Ongoing Agenda - World Bank Group (World Bank, Washington, DC, 2018)
Lao PDR’s GDP growth slightly decelerated to 6.9 percent in 2017, but remained robust. The economy is expected to further ease to 6.7 percent in 2018. Recent expansion of labor-intensive industries (agriculture, manufacturing and services) and robust remittances inflows are expected to continue to support poverty reduction. Macroeconomic vulnerabilities remain significant despite some improvement in economic management. The large deficit has resulted in public debt reaching around 61 percent of GDP in 2017. The current account deficit narrowed in 2017 on the back of strong exports of electricity, manufacturing and agriculture products, while improved metal prices supported higher mining exports. Monetary conditions were slightly loosened near the end of 2017; however, the monetary policy transmission mechanism remains weak. The fiscal deficit is expected to gradually decline while the external deficit will temporary widen. These and other economic developments and the economic outlook are discussed in the first section of this report. The second section focuses on the high cost of paddy production for farmers and the operational inefficiencies among multiple players in the value chain that are responsible for high consumer rice prices. The study finds that Lao farmers receive relatively high farm-gate price, yet high production cost eats their profits. These constraints are largely structural and they require: (i) facilitating value chain linkages between farmers and millers through productive partnerships; (ii) enhancing access to finance of farmers and millers; and (iii) improving quantity and quality of public services critical to reduce the currently high production costs and enhance commercialization, e.g., seed, applied research, mechanization, cooperatives, and good agricultural practices. Reducing farm production costs appears to be the most important challenge and opportunity at this point of time for Lao PDR.